A major practicum report for General Tuna Corporation Bo. Tambler, General Santos City - Abaniel, Jazzette Marie de Jesus (2006)
The major plant practice was conducted at General Tuna Corporation for a total of 288 hours. The author was supervised under the Quality Control Department where she was assigned in particular to the pouch line. There she monitored the fill weight, net weight, formulation ingredients, and packed products sensory evaluation and conducted as well the burst test, load test, and load test of pouch bags. She also observed other things that have to be checked by a quality control inspector for safety and quality of pouched products. Some problems were also encountered in the pouch line and the author was able to see how these were remedied and fixed. Outside the pouched area, she was able to grasp the general activities taking place as she had been assigned for a time in almost all the necessary areas of production. The author learned a lot in the practicum not only the technical aspect but the social part as well